1991
DOI: 10.1093/oxfordjournals.humrep.a137258
|View full text |Cite
|
Sign up to set email alerts
|

An investigation by mathematical modelling of whether mouse and human preimplantation embryos in static culture can satisfy their demands for oxygen by diffusion

Abstract: Mammalian preimplantation embryos are conventionally grown in small, static droplets of medium. By contrast, embryos within the oviduct are subject to mixing forces arising from the action of cilia and the contractions of the myosalpinx. Such forces will minimize the buildup of unstirred layers around the embryos and facilitate the exchange of gases and metabolites. We have devised a mathematical model to investigate whether preimplantation mouse and human embryos grown in static culture can satisfy their requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Warburg's (1923) model assumes that concentration is constant in a plane and varies in the direction normal to the plane. More recently, the spherically symmetric form of the steady-state diffusion equation has been employed for modelling oxygen concentrations in ovarian follicles (Gosden & Byatt-Smith 1986) and in preimplantation embryos in static culture (Byatt-Smith et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warburg's (1923) model assumes that concentration is constant in a plane and varies in the direction normal to the plane. More recently, the spherically symmetric form of the steady-state diffusion equation has been employed for modelling oxygen concentrations in ovarian follicles (Gosden & Byatt-Smith 1986) and in preimplantation embryos in static culture (Byatt-Smith et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Gosden & Byatt-Smith 1986, Byatt-Smith et al 1991 is to solve a diffusion-equation model with the rate of oxygen consumption assumed to be constant or proportional to the oxygen concentration. This assumption allows analytical solution of the governing equations.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…More convincingly, incubation in 5% O 2 compared with 20% O 2 increases oxygen uptake and pyruvate oxidation (Hooper et al, 2001). This finding is significant as the effect of a reduction in O 2 tension from atmospheric levels to 5% within embryos has also been examined using a mathematical model (Byatt-Smith et al, 1991). Byatt-Smith et al (1991) showed that for small mammalian embryos, such as mouse embyros, O 2 from a 5% atmosphere would be able to sustain oxidative phosphorylation throughout development, albeit under hypoxic conditions.…”
Section: Manipulation Of Substrates and Metabolic Pathways During Devmentioning
confidence: 99%
“…This finding is significant as the effect of a reduction in O 2 tension from atmospheric levels to 5% within embryos has also been examined using a mathematical model (Byatt-Smith et al, 1991). Byatt-Smith et al (1991) showed that for small mammalian embryos, such as mouse embyros, O 2 from a 5% atmosphere would be able to sustain oxidative phosphorylation throughout development, albeit under hypoxic conditions. However, larger embryos, such as human or cattle embryos, would establish a significant gradient leading to anoxia in the centre of the embryo, which may explain some of the metabolic differences among embryos of different species.…”
Section: Manipulation Of Substrates and Metabolic Pathways During Devmentioning
confidence: 99%
“…As shown in a mathematical model by ByattSmith et al [3], the culture of human embryos in a static microdrop may become marginally hypoxic, especially at lower oxygen levels (5 % O 2 ).…”
Section: Discussionmentioning
confidence: 99%